Clinical effect of the high insertion torque on dental implants: A systematic review and meta-analysis - Lemos, Cleidiel A.A.; Verri, Fellippo R. [UNESP]; de Oliveira Neto, Olavo B.; Cruz, Ronaldo S. [UNESP]; Luna Gomes, Jéssica M. [UNESP]; da Silva Casado, Bruno G.; Pellizzer, Eduardo P. [UNESP] (Elsevier, 2020)
Statement of problem: A consensus on the clinical performance in dental implants placed with different insertion torques is lacking. Purpose: The purpose of this systematic review and meta-analysis was to evaluate the effect of high insertion torque compared with regular or low torques during dental implant placement in terms of implant survival rate and marginal bone loss. Material and methods: Two independent reviewers searched electronic databases for studies published until April 2019. The population, intervention, comparison, outcome (PICO) question was “Do patients who receive implants with a high torque (equal or higher than 50 Ncm) show similar implant survival rates and marginal bone loss as compared with those who receive implants with a regular or low torque (less than 50 Ncm)?”. The meta-analysis was based on the Mantel-Haenszel (MH) and the inverse variance (IV) methods (α=.05). Results: The search yielded 6 articles, which included 389 patients (mean age: 55.28 years) who had received 651 dental implants (437 with high torque and 214 with low or regular torque). Most studies evaluated delayed loading, except 1 study that evaluated immediate implant loading (n=50 for each group). Low or regular insertion torque had a high failure rate (4.2%) compared with high insertion torque (1.1%), chiefly because of immediate loading. However, the meta-analysis indicated no significant difference between high- and regular- or low-torque implant placement in implant survival rate (P=.52, risk ratio [RR]: 0.51, 95% confidence interval [CI]: 0.06-4.06) and marginal bone loss (P=.30, mean difference [MD]: 0.15, 95% CI: -0.14 to 0.44). Conclusions: A high insertion torque during implant placement does not affect implant survival rate or marginal bone loss. However, further research is recommended to reassess this clinical performance.